INtimal hyPerplasia evAluated by oCT in de novo COROnary lesions treated by drug-eluting balloon and bare-metal stent (IN-PACT CORO): study protocol for a randomized controlled trial - Burzotta Francesco (Trials, 2012)
Abstract Background Neointimal hyperplasia plays a pivotal role in the pathogenesis of in-stent restenosis in patients undergoing percutaneous coronary interventions. Drug-eluting balloons are a promising tool to prevent restenosis after coronary angioplasty. Moreover, an increased knowledge of the pathophysiology of restenosis my help improve therapeutic strategies. Methods/Design We present the design of an open-label, randomized three-arm clinical trial aimed to assess whether a strategy of bare-metal stent implantation with additional use of drug-eluting balloons, either before (pre-dilation) or after stenting (post-dilation), reduces the primary endpoint of in-stent neointimal hyperplasia area as compared with a strategy of bare-metal stent implantation alone. This primary endpoint will be assessed by optical coherence tomography at follow-up. Secondary endpoints will be the percentage of uncovered struts, and the percentage of struts with incomplete apposition. An ancillary study investigating the relation between systemic levels of endothelial progenitors cells and neointimal hyperplasia, and the interaction between endothelial progenitors cell levels and drug-eluting balloons has been planned. Thirty consecutive patients undergoing percutaneous coronary intervention will be randomized with a 1:1:1 design to bare-metal stent implantation alone (n = 10); bare-metal stent implantation after pre-dilation with a drug-eluting balloon (n = 10); or bare-metal stent implantation followed by post-dilation with a drug-eluting balloon (n = 10). Six-month follow-up coronary angiography with optical coherence tomography imaging of the stented segment will be performed in all patients. Blood samples for the assessment of endothelial progenitors cell levels will be collected on admission and at 6 months. Discussion Experimental and early clinical data showed that inhibition of neointimal hyperplasia may be obtained by local administration of antiproliferative drugs loaded on the surface of angioplasty balloons. The INtimal hyPerplasia evAluated by oCT in de novo COROnary lesions treated by drug-eluting balloon and bare-metal stent (IN-PACT CORO) trial was conceived to test the superiority of a strategy of bare-metal stent implantation with additional drug-eluting balloon use (either before or after stenting) versus a strategy of bare-metal stent implantation alone for the reduction of neointimal hyperplasia. We also planned an ancillary study to assess the role of endothelial progenitors cells in the pathophysiology of neointimal hyperplasia. Trial registration Clinicaltrials.gov NCT01057563.